Global structure of four-way RNA junctions studied using fluorescence resonance energy transfer. - Walter, F (1998)
Four-way helical junctions are found widely in natural RNA species. In this study, we have studied the conformation of two junctions by fluorescence resonance energy transfer. We show that the junctions are folded by pairwise coaxial helical stacking, forming one predominant stacking conformer in both examples studied. At low magnesium ion concentrations, the helical axes of both junctions are approximately perpendicular. One junction undergoes a rotation into a distorted antiparallel structure induced by the binding of a single magnesium ion. By contrast, the axes of the four-way junction of the U1 snRNA remain approximately perpendicular under all conditions examined, and we have determined the stacking conformer adopted.